2017
DOI: 10.1515/jwld-2017-0068
|View full text |Cite
|
Sign up to set email alerts
|

The change of quantity and quality outflow of water in Ochożanka River basin

Abstract: The aim of this research work is to evaluate changes in the quantities of water and chemical parameters of outflow water from the forest catchment. Research was carried over a hydrological five-year period in the Ochożanka River basin (Western Polesie). The structure of the catchment area of 33.1 km 2 is dominated by forestland constituting 81% of the area. During this period the precipitation amounted to 627 mm, which was 100 mm higher than the multi-year average. Precipitation of the summer half-year was alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This is connected with oxidoreduction reactions and self-purification processes in river waters. A high level of COD is associated with the presence of organic substances in the water, which undergo direct oxidation using oxygen contained in the water, or biochemical conversion to inorganic compounds with the participation of microorganisms, using oxygen absorbed from the water [49][50][51]. The research demonstrated that COD concentration increased downstream, which may be related to the accumulation of organic pollutants of municipal and agricultural origin [52].…”
Section: Discussionmentioning
confidence: 94%
“…This is connected with oxidoreduction reactions and self-purification processes in river waters. A high level of COD is associated with the presence of organic substances in the water, which undergo direct oxidation using oxygen contained in the water, or biochemical conversion to inorganic compounds with the participation of microorganisms, using oxygen absorbed from the water [49][50][51]. The research demonstrated that COD concentration increased downstream, which may be related to the accumulation of organic pollutants of municipal and agricultural origin [52].…”
Section: Discussionmentioning
confidence: 94%
“…The hydrological response of a watershed depend on physical environment and climate, on the one hand, and on its physical environment, on the other [GRZYWNA 2017]. Numerous parameters shape the appearance and evolution of a flood; the most important factors are, among others: topography, land use, soil type, human action, and others.…”
Section: Introductionmentioning
confidence: 99%